Neopentecostalism and Politics: The ‘Cultural Battle’ of the Nueva República Party and Its Impact on Sexual and Reproductive Rights in Costa Rica (2018–2024) - Barrantes Rodríguez, Stephanie (2025)
Introduction: This article examines the characterization of neo-Pentecostalism in Costa Rica and its implications for women's sexual and reproductive rights arising from the presence of political groups linked to certain religious groups. Objective: To analyze, from a critical human rights theory perspective, the interrelationship of the concepts of cultural warfare and gender ideology present in the political interventions and practices of the New Republic Party and their impact on women's sexual and reproductive rights. Methodology: Qualitative research whose data was collected through research diaries and consultation with documentary sources such as print media, social media, audiovisual materials, conferences, participant observations in churches, and related literature. Results: The group's positioning motivates a series of political discourses and interventions that hinder the recognition and implementation of public policies and education on sexual and reproductive health issues. Conclusions: The politicized mobilization of faith in matters of human rights promotes actions and discourses that condition the recognition of human rights to certain social roles and behaviors. The reversal of human rights present in these narratives constructs a social and political environment of non-recognition and symbolic violence against women's rights.